Fiber optic displacement sensor for measurement of glucose concentration in distilled water - Yasin, M.; Harun, Sulaiman Wadi; Yang, H.Z.; Ahmad, Harith (National Institute of Optoelectronics, 2010)
A simple intensity modulated displacement sensor is proposed and demonstrated for sensing the concentration of glucose in distilled water. For a concentration change of glucose from 0 to 25 % in distilled water, the peak light intensity and its position increases linearly with the concentration due to the increased of the refractive index of the liquid. The measured sensitivities are obtained at around 0.0103 mV/(%) and 0.0229 mm/(%) for the peak voltage and position changes respectively. The stability, high sensitivity and simplicity of the sensor make it suitable for chemical, pharmaceutical, biomedical and process control sensing applications.